Implementation of Indonesian National Education Policy to Enhance Equitable Access and Educational Quality: A Pesantren Education Perspective - Idam Mustofa; Ahmad Saifulloh; Abu Darda; Syarifah Syarifah; Wahyu Setiawan (JUMPA : Jurnal Manajemen Pendidikan, 2025)
The implementation of national education policies within Indonesia's plural education system faces significant challenges due to the diverse institutional characteristics of its educational institutions. This study aims to analyze the implementation of national education policies in improving equitable access and educational quality through the perspective of Islamic boarding schools (pesantren) as an analytical lens. The research employed a qualitative policy analysis approach using document analysis of national education regulations, government policy documents, official reports, and relevant scholarly publications. Data were analyzed through qualitative content analysis using Edwards III's policy implementation model, which emphasizes four key variables: communication, resources, disposition, and bureaucratic structure. The findings indicate that these four variables remain relevant for explaining policy implementation. However, within the context of pesantren, policy implementation is also influenced by institutional characteristics, the leadership of kiai, distinctive funding mechanisms, coordination between the Ministry of Primary and Secondary Education and the Ministry of Religious Affairs, and innovation diffusion in the policy adoption process. These findings suggest that national education policy implementation in pesantren cannot be understood using the same approach applied to formal schools. This study contributes conceptually by extending Edwards III's implementation model through the integration of pesantren institutional characteristics and innovation diffusion mechanisms as contextual factors influencing policy implementation within Indonesia's plural national education system. The findings are expected to inform the development of more adaptive education policies that accommodate institutional diversity.